Pengaruh Penggunaan Media Video Terhadap Minat dan Hasil Belajar Siswa Kelas XI pada Pelajaran PAI di SMA YPI Tunas Bangsa Palembang - Feri Ardiansah (Tarbawy : Jurnal Pendidikan Islam, 2018)
This research aims to find whether there is a video of the interests and influence learning outcomes, and to determine the relationship of interest in learning to student learning outcomes. The method used in this research is true experimental design with design pretest-posttest control group design. Cluster sampling technique with random sampling. Experimental class gets lesson using video media, media control class does not use video. Techniques of data collection using questionnaires and tests. To determine the effect of video on learning interest in this research using the t test, because the test results are statistically significant, so we can reject the null hypothesis that there is no difference in the average video effect to the interest in studying the experimental group and the control group. For video effect on learning outcomes using t-test, because it tests the results are statistically significant, so we can accept the alternative hypothesis that there are differences in average learning outcomes experimental group and the control group. The third hypothesis test results there is a positive relationship between interest and learning outcomes. Based on the discussion, the authors recommend the school to strive to complete the equipment or media for the smooth process of learning, motivating teachers to improve learning and creativity in creating fun, the results of this research can be made in consideration for our future research in developing and expanding the scope of media learning Islamic education.